How social ventures successfully mobilize resources - Goetze, Lauren (Graduate School of Business (GSB), 2025)
Social ventures are a powerful force for socioeconomic development and self-determination around the world. However, resource scarcity places severe constraints on their impact. Existing literature has not yet adequately explored several key aspects of this phenomenon, leading to limited applicability and effectiveness of current theory. This research endeavors to answer the central question: How do social ventures leverage different resourcing strategies to overcome resource scarcity? Related lines of inquiry are included to answer the sub-questions: What are the implications of different resource mobilization strategies? What effect does context have on social ventures' resource mobilization strategies? By developing four organizational case studies across two countries that have successfully mobilized resources, this study builds understanding of what resource mobilization strategies are most effective. The analysis of the qualitative data followed the abductive approach and aligned with the constructivist paradigm. This method allowed for the centering of participants' perspectives, and exploration of the process of resource mobilization. The findings highlight social capital as the most impactful and widely applicable resource mobilization strategy. After applying the Social Cohesion Perspective to the data, it was evident that two divergent approaches to social capital are present among the cases, with one approach centering bonding and bridging social capital, and the other relying on linking social capital. While both approaches have distinct tradeoffs, linking social capital dependence is shown to fuel a chain reaction of mission drift and degradation of bonding and bridging social capital. Meanwhile, strong networks of bonding social capital, combined with bridging social capital, facilitate continued mission alignment and organizational adaptability. Additionally, this later strategy contributes to increased utilization of bricolage practices to mobilize resources. Finally, the complex effects context exerts on social capital are outlined, showing particularly strong impacts on bonding and linking social capital. This research contributes to theory by expanding the Social Cohesion Perspective, outlining key implications of different resource mobilization strategies which highlight the importance of diversified resource bases. The findings also show that dependence on linking social capital leads organizations towards a potentially hazardous sequence of events driven by mission drift. Further expansion on this theory includes the effects of context on various forms of social capital as well as the process of resource mobilization, and bricolage's ties to social capital.